The sound of a wild snail eating - Bailey, Elisabeth Tova (Chapel Hill, North Carolina : Algonquin Books of Chapel Hill, 2010)
In a work that beautifully demonstrates the rewards of closely observing nature, Elisabeth Bailey shares an inspiring and intimate story of her uncommon encounter with a "Neohelix albolabris"--A common woodland snail.
Part 1. The violet-pot adventures. Field violets ; Discovery ; Explorations -- Part II. A green kingdom. The forest floor ; Life in a microcosm ; Time and territory -- Part III. Juxtapositions. Thousands of teeth ; Telescopic tentacles ; Marvelous spirals ; Secret recipes -- Part IV. The cultural life. Colonies of hermits ; Midnight leap ; A snail's thoughts ; Deep sleep -- Part V. Love and mystery. Cryptic life ; Affairs of a snail ; Bereft ; Offspring -- Part VI. Familiar territory. Release ; Winter snail ; Spring rain ; Night stars -- Appendix: Terraria.
Simultaneously published: [Markham, Ontario] : Thomas Allen & Son.
Includes bibliographical references (pages 179-186).
105643
Keywords: Bailey, Elisabeth Tova -- Health; Snails as pets -- Anecdotes; Neohelix albolabris -- Anecdotes; Gastropoda -- Physiology; Gastropoda -- Anatomy; Chronically ill -- Biography; Snails as pets -- Anecdotes; Snails; Chronic Disease; Sick -- Biography; Autobiography